Narrating Our History: Selections from a Dialogue among Queer Media Artists from the African Diaspora - Ferrera-Balanquet, Raúl; Harris, Thomas Allen; Frilot, Shari; Gilliam, Leah; Suggs, Dawn; Taylor, Jocelyn; Welbon, Yvonne; Juhasz, Alexandra (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The first time I spoke in public about my work was during the Los Angeles Lesbian and Gay Festival in 1990. Cheryl Dunye was the only other woman of color on the panel. When I asked a question regarding funding, I naïvely stated that funding was not a prob lem for me considering the fact that my work at that time was of medium to low production quality. I had minimal access to a low-end production facility, and my piece was only five minutes long. I was alluding to the fact that it has been “easy” for me.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Cuerpo, género y representación en el videoarte ecuatoriano (1998-2012) - Mantilla, Christian León (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2016)
Este texto reflexiona sobre los discursos e imaginarios de género y sexualidad que se producen dentro del campo del videoarte realizado en Ecuador entre 1998 y 2013. Desde finales de los noventa, hay una presencia de videos que abordan temáticas de cuerpo, política, deseo, violencia, roles e identidad que posicionan nuevos temáticas, lugares de enunciación y sujetos través de las tecnologías de video. A través de un conjunto de obras emblemáticas, el texto analiza los discursos y las estrategias visuales con las cuales se construyen feminidades, masculinidades y diversidades sexuales en el contexto contemporáneo. Está producción plantea un relato alternativo frente a las tendencias dominantes dentro de la historia del arte ecuatoriano. Muestra las nuevas sensibilidades y sujetos que se afirman a través del uso de tecnologías de video. This paper reflects on the speeches and imaginary of gender and sexuality that occur within the field of video art made in Ecuador between 1998 and 2013. Since the late nineties, there is a presence of vid-eos that address issues of body politics, desire, vio-lence, roles and identity that position new themes, places and subjects of enunciation through video technologies. Through a set of emblematic works, the text analyzes the speeches and visual strategies which femininity, masculinity and sexual diversities are built in a contemporary context. This production presents an alternative story against the dominant trends in the history of Ecuadorian art. It shows the new sensibilities and subjects that are affirmed through the use of video technology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé